4-H Wildlife Habitat Evaluation Program (WHEP): Learn about wildlife ecology and management - Sarah Webb Miller; Mark E. Hostetler (EDIS, 2003)
The Wildlife Habitat Evaluation Program (WHEP) is a 4-H youth natural resource program dedicated to teaching wildlife and fisheries habitat management to junior and senior level youth (ages 8-19). WHEP fosters relationships between youth, professional wildlife and fisheries biologists, parents, teachers, volunteers, farmers, and ranchers. WHEP is a nationally recognized program and won the 1996 Wildlife Society Conservation Education Award. As with all 4-H programs, WHEP teaches essential life skills such as oral and written communication, critical thinking, teamwork, and decision-making. This document is Factsheet WEC 175, one of a series of the Department of Widlife Ecology and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences (IFAS), University of Florida. First published in October 2003.